Predicting numerical achievement in the high jump using the Fosbury Flop method based on the lower limb length measurements of advanced athletes (Journal of the College of Basic Education, 2025)
The body's structural composition and body measurements play a significant and important role in athletic performance and are considered one of the foundations for the success or failure of an athlete's activity. The availability of appropriate body measurements for a particular activity gives the athlete a greater opportunity to understand the correct motor performance of skills. Since the high jump is one of the track and field events that has witnessed rapid development in its performance, the researchers decided to choose the "fosbury flop" method for the high jump. The importance of the research lies in attempting to develop prediction equations for the numerical achievement in the high jump using the "fosbury flop" method for advanced players, based on the lengths of the lower limbs. The research aims to identify the predictive equations for the numerical achievement in the high jump using the "fosbury flop" method for advanced players, based on the measurements of the lengths of the lower limbs. The researchers used a descriptive approach using a survey method on (14) high jump players using the "fosbury flop" method. (4) measurements were calculated for lower extremity lengths (leg length, thigh length, shin length, and foot length). The numerical achievement of advanced players in the high jump (fosbury flop) was also adopted. The ready-made program (IBM SPSS Vr25) was used to process the data, and a set of conclusions and recommendations were reached.